The Effect of Work Engagement and Psychological Empowerment on Employee Performance with Organizational Citizenship Behavior as a Mediating Variable - Dealisa, Laora; Widodo, Slamet (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to analyze the influence of work engagement, and psychological empowerment on Organizational Citizenship Behavior (OCB) and employee performance as well as analyze the mediating role of OCB on the influence of work engagement and psychological empowerment on performance. This research is quantitative (survey). The type of data used is primary data obtained through distributing questionnaires. The respondents for this research were 255 employees of the Regional Government of Bengkulu Province. The data was analyzed using descriptive analysis and PLS analysis with the help of the SmartPLS version 3 application. Based on research in the field, the results obtained were: (1) The effect of work engagement on employee performance is significant; (2) The effect of psychological empowerment on employee performance is not significant; (3) OCB has a positive effect on performance; (4) The effect of work engagement on OCB is significant; (5) The effect of psychological empowerment on OCB is significantly positive; (6) OCB mediates the effect of work engagement on performance. The mediation role is partial mediation; (7) OCB mediates the effect of psychological empowerment on performance. This study contributes to the development of knowledge related to work engagement, psychological empowerment, and OCB.